1997
DOI: 10.1159/000150567
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy of Herpes simplex and Varicella-zoster Virus Infections

Abstract: Antiviral treatment of herpesvirus infections is rapidly changing since the advent of new drugs with improved oral availability. The efficacy of valaciclovir, the prodrug of aciclovir, and famciclovir, the prodrug of penciclovir, in the treatment of herpes genitalis and acute herpes zoster has been well documented in large clinical trials. Both drugs are effective on zoster-associated pain. Brivudin and sorivudine which are the most active compounds against varicella-zoster virus (VZV) in cell culture have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 62 publications
1
48
0
1
Order By: Relevance
“…We have used a three-dimensional epithelial culture system which promotes the differentiation of human keratinocytes. In HSV-and VZV-infected organotypic epithelial raft cultures, we observed cytopathic changes identical to those found in the squamous epithelium in vivo, including the formation of typical intraepi- Compounds known for their activity against HSV and VZV, e.g., ACV, PCV, BVDU, PFA, and CDV (8,21,28), were tested in monolayers of PHKs and in organotypic epithelial raft cultures. Antiviral assays in monolayers of PHKs, showed that IC 50 values obtained in PHKs were higher than those we have previously reported for human embryonic fibroblasts.…”
Section: Discussionsupporting
confidence: 52%
“…We have used a three-dimensional epithelial culture system which promotes the differentiation of human keratinocytes. In HSV-and VZV-infected organotypic epithelial raft cultures, we observed cytopathic changes identical to those found in the squamous epithelium in vivo, including the formation of typical intraepi- Compounds known for their activity against HSV and VZV, e.g., ACV, PCV, BVDU, PFA, and CDV (8,21,28), were tested in monolayers of PHKs and in organotypic epithelial raft cultures. Antiviral assays in monolayers of PHKs, showed that IC 50 values obtained in PHKs were higher than those we have previously reported for human embryonic fibroblasts.…”
Section: Discussionsupporting
confidence: 52%
“…However, differences of less or comparable magnitude are regarded as both biologically and clinically significant in a variety of clinical studies of new antiviral drugs against herpes. 10,11,[39][40][41][42][43][44][45] Thus, the difference between 23% reactivation in COX-2-treated mice compared to 54% in control, untreated mice seen in our study is biologically and likely clinically significant if translated to humans. It may be that a combination of an antiviral drug, such as acyclovir, and celecoxib, a COX-2 inhibitor, would either additively or synergistically enhance the level of inhibition of viral reactivation.…”
Section: Discussionmentioning
confidence: 56%
“…Enzephalitiden werden bei immunsupprimierten Patienten häufig beobachtet. Da mit den Nukleosidanaloga Aciclovir, Brivudin, Famciclovir und Valaciclovir mehrere wirksame Virostatika fĂźr die Behandlung des Zosters zur VerfĂźgung stehen [21], ist eine schnelle und sichere Diagnosestellung von zunehmender Bedeutung. DarĂźber hinaus kĂśnnen bei frĂźhzeitigem Therapiebeginn spätere Komplikationen, insbesondere die PZN, zum Teil verhindert werden [11].…”
Section: Besprechungunclassified